AB1313 Survival of leflunomide treatment in a cohort of patients with rheumatoid arthritis. (23rd January 2014) - Rodríguez, A.B.; Fontseré, Ó.; Peña, R.; Toledano, E.; Blanco, M.; Pato, E.; Abasolo, L.; Morado, I.; Jover, J. Ά.
Abstract : Background: after more thana decade usingLeflunomide(LFN), is widely known to be effective in the treatment of rheumatoid arthritis (RA). However, there is evidence in the literatureofa higher rate of suspension for toxicity and lack of efficacy compared to other DMARDs such as methotrexate (MTX). Although, those are series with small numbers of patients and short-term follow up. Objectives: toevaluate the survival of LFN, and the causes of its suspension in a cohort of patients with RA. Methods: retrospectivelongitudinal observational study. Subjects: patients with RA followed in our hospital, treated with LFN, from January 1, 2006 until October 1, 2011. Outcomes: primary outcome: LFN suspension due to: a) adverse event (AE), b) lack of efficacy, c) patient's decision; d) remission or improvement. Secondary outcomes: age, sex, date of diagnosis, date of start and end of treatment with LFN. The data sourcewas our electronic health record. Statistical analysis: a description of the sociodemographic and clinical characteristics of patients included and the causes for suspension using frequency distribution rates and the mean and standard deviation or median and percentiles. Survival techniques are used to estimate the suspension rate of LFN, expressing the incidence per 1000 patient-years (95% CI). Results: 322 patients started treatment with LFN during the follow up. 257 were women (79.81%), the mean age at baseline was 59±15 years. The median time from diagnosis of RA was 2.37 years (p25-75: 0, 56-5, 68), there were 116 suspensions (38.41%), the 68.97% of them were due to AE, 7.76% to patient's decision, 7.76% due to lack of efficacy, and 6.9% to clinical improvement. 74.78% of the patients with suspensions were women, mean age at the time of suspension was 60±15 years and the median time from diagnosis of RA was 2.64 years (P25-75: 0.73-5.68). The suspension rate was 216 per 1000 (95% CI 180.23-259.35), 277.88 per 1000 in men (95% CI 193-399.88) and 199 per 1000 in women (95% 161-245.87). 83 of the suspensions (71.5%) occurred within the first 6 months of treatment with LFN. 50% of patients had discontinued the drug 3.5 years after starting treatment. AE rate was 149.10 per 1000 (95% CI 119.76-185.636). The suspension rate associated with lack of efficacy was 16.77 per 1000 (95% CI 8.72-32.23). The suspension rate because of clinical improvement was 14.91 per 1000 (95% CI 7.45-29.81). Conclusions: the survival of the treatment with LFN is less than 50% at 4 years. The suspension rate was high, mainly due to adverse events. Disclosure of Interest: None Declared